2019
DOI: 10.1038/s41598-019-46613-x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis and codominant markers development in caper, a drought tolerant orphan crop with medicinal value

Abstract: Caper ( Capparis spinosa L.) is a xerophytic shrub cultivated for its flower buds and fruits, used as food and for their medicinal properties. Breeding programs and even proper taxonomic classification of the genus Capparis has been hampered so far by the lack of reliable genetic information and molecular markers. Here, we present the first genomic resource for C. spinosa , generated by transcriptomic approach and de novo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 126 publications
0
13
1
Order By: Relevance
“…Although these markers are species specific, the increasing accessibility to next-generation sequencing 41 has enabled the development of SSRs for the so-called orphan, neglected or wild crop relative species (e.g. [42][43][44][45] ), although sequencing large plant genomes still remains a challenge 46 .…”
mentioning
confidence: 99%
“…Although these markers are species specific, the increasing accessibility to next-generation sequencing 41 has enabled the development of SSRs for the so-called orphan, neglected or wild crop relative species (e.g. [42][43][44][45] ), although sequencing large plant genomes still remains a challenge 46 .…”
mentioning
confidence: 99%
“…Recent work indicated that the nucleotide metabolism pathway was an important pathway for D. wangliangii to adapt to drought stress (Zhao et al, 2019). The IMPHD gene was reported as the rate-limiting enzyme of guanine nucleoside biosynthesis, directly affecting the biosynthesis of guanine, xanthine, and hypoxanthine (Mercati et al, 2019). In DSA vs. DSB, the IMPHD gene was upregulated, and the content of guanine, xanthine, and hypoxanthine increased.…”
Section: Underlying the Responses Of Phenylpropanoid Biosynthesis And Purine Metabolism In D Sinense To Drought Stressmentioning
confidence: 99%
“…This list includes 39 plant species having good performances under harsh environmental conditions, being able to overcome at least one out of four severe stress factors, i.e., two edaphic (low soil nutrient content and high soil salinity) ad two climatic (lack of water and extreme thermic events). In particular, Capparis species can be considered well adapted to harsh climatic and edaphic conditions (Mercati et al, 2019), with Capparis sicula showing a high ecological plasticity, as it can survive both in poorly aerated, salty and clayey soils as well as in secondary habitats such as roadsides (Gristina et al, 2014), while C. spinosa mainly colonizes coastal rocky cliffs. Wild cabbages (Brassica spp.)…”
Section: Good Performers and Stress-tolerant Sicilian Nwfpmentioning
confidence: 99%